2002
DOI: 10.1016/s0378-7788(02)00005-1
|View full text |Cite
|
Sign up to set email alerts
|

Thermal comfort in naturally ventilated buildings: revisions to ASHRAE Standard 55

Abstract: Recently accepted revisions to ASHRAE Standard 55-thermal environmental conditions for human occupancy, include a new adaptive comfort standard (ACS) that allows warmer indoor temperatures for naturally ventilated buildings during summer and in warmer climate zones. The ACS is based on the analysis of 21,000 sets of raw data compiled from field studies in 160 buildings located on four continents in varied climatic zones. This paper summarizes this earlier adaptive comfort research, presents some of its finding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
425
0
48

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 1,081 publications
(541 citation statements)
references
References 7 publications
8
425
0
48
Order By: Relevance
“…Arens et al suggest that the EN15251-2007 categories for thermal comfort do not align with perceptible changes in occupant satisfaction and may lead to more energy intensive buildings [47]. Extensive research has shown that at least for thermal comfort and lighting, occupants can be satisfied over a wide range of conditions (thermal comfort: [60][61][62]; lighting: [63,64]). Additionally, there are potential economic implications associated with tighter levels of control, both in design and operation.…”
Section: Assessment Class Limits Are Controversialmentioning
confidence: 99%
“…Arens et al suggest that the EN15251-2007 categories for thermal comfort do not align with perceptible changes in occupant satisfaction and may lead to more energy intensive buildings [47]. Extensive research has shown that at least for thermal comfort and lighting, occupants can be satisfied over a wide range of conditions (thermal comfort: [60][61][62]; lighting: [63,64]). Additionally, there are potential economic implications associated with tighter levels of control, both in design and operation.…”
Section: Assessment Class Limits Are Controversialmentioning
confidence: 99%
“…On the other hand, the adaptive model, states that factors beyond fundamental physics and physiology play an important role in building occupants' expectations and thermal preferences. The way people interact with the environment, their behaviour changes can modify their thermal expectations [36,37]. Figure 8 presents the adaptive thermal comfort levels of the master bedroom, according to EN 15251 (CYS EN 2007) [38].…”
Section: Impact Of Night Ventilation On Thermal Comfortmentioning
confidence: 99%
“…Fully air-conditioned buildings are also excluded from the standard. The comfort standard has a mean comfort zone band of 5K for 90% acceptance, and another of 7K for 80% acceptance, both centred around the optimum comfort temperature (T comf ) (Equation 3) [9].…”
Section: 1mentioning
confidence: 99%
“…Such local initiatives raise the question if models of adaptive thermal comfort should be introduced in moderate thermal climate zones since they obviously have most impact in hot climate zones [9]. Therefore this paper focuses on the impact of the introduction of adaptive thermal comfort evaluation criteria in moderate thermal climate regions, especially the marine climates labelled Cfb and Cfc according to the Köppen-Geiger-Pohl classification [12], in terms of usability and energy use.…”
mentioning
confidence: 99%
See 1 more Smart Citation